Pemanfaatan Powerpoint dan Ispring Suite Dalam Mendesain Game Edukasi Sebagai Media Pembelajaran Matematika Berbasis Android - Hala, Natalia Alfriyanti Barek; Blegur, Irna Karlina Sensiana; Garak, Siprianus Suban (Tematik : Jurnal Konten Pendidikan Matematika, 2023)
In this era, the integration of technology in learning needs to be done by the teacher so that it fits the needs of students. Therefore, teachers are required to be able to facilitate learning in class in accordance with various existing developments. The use of Android-based learning media is one way to utilize technology in learning. This article is a literature study that discusses the use of powerpoint and ispring suite to create an Android-based mathematics learning media that is packaged in educational games. Educational games are digital learning media that are designed to be attractive and interactive to assist educators and students in conveying and understanding the material to be provided during learning. Furthermore, how games can educate students in learning mathematics is also discussed in this article.